The health benefits of UV radiation exposure through vitamin D production or non-vitamin D pathways. Blood pressure and cardiovascular disease - Weller, Richard B (Photochemical & photobiological sciences, 2017)
The detrimental effects of ultraviolet radiation are well known. Skin cancer, photo-aging, and induction or exacerbation of photosensitive dermatoses have been the focus of most photobiological research since 1928 when Findlay confirmed the carcinogenicity of ultraviolet radiation using a murine model of skin cancer. The epidemiological, mechanistic and clinical trial data have enabled the classification by the International Agency for Research on Cancer of ultraviolet radiation as a Group 1 ('sufficient evidence') carcinogen for human skin. Public health advice in most developed countries with a pale-skinned population following this has advocated limiting exposure to sunlight through use of clothing, sunblock and behavioural alterations. Despite this plethora of data, one striking omission is evidence that ultraviolet radiation shortens life, and as I will lay out in this chapter, epidemiological and now mechanistic data suggest that UV may have significant benefits on health and in particular cardiovascular health. UV photoreduces nitrogen oxides sequestered in the skin. The resulting NO moves to the systemic circulation where it vasodilates and lowers BP.